(untitled) (Saptagandaki Journal, 2017)
Firm financing and investment policies are central to the study of corporate finance. In imperfect capital market, financing and investment policies of enterprises are dependent to each other. Firm’s investment decisions depend upon the access and availability of finance in capital market. But various capital market frictions like information and incentives wedge the efficient allocation of fund to each of marginally profitable project. Consequently, in asymmetric informational theoretic framework, firms change their strategies in raising their capital. Firms’ first best choice for financing their investment in severity of information problem, rests on their internal funds since it is the cheapest and more unrestricted source of finance to the managers. To this milieu, this paper focuses on investigating whether the Nepalese enterprises depend on their internal funds to finance their investment or not? World Bank Enterprise Survey data set are employed to examine the investment and financing policies of Nepalese enterprises. The data set consist of financial information of 968 firms across multiple size, sector and age category. We employ simple measures of descriptive statistics like frequencies, percentage and arithmetic mean viz; the average of a set of numerical values to analyze the data by sorting the observations to various portfolios. The study result confirms that the firms heavily depend on their internal funds to finance their investment. These results are consistent with prior literatures for example; Fazzari, Hubbard, & Peterson (1988), Gilchrist & Himmelberg (1995), Hu & Schiantarelli (1998) etc when observed in cross section of size, sector, age and ownership pattern of enterprises. The Saptagandaki Journal Vol.8 2017: 47-55